Unique immunomodulatory effect of paeoniflorin on type I and II macrophages activities - Tianhang Zhai; Yue Sun; Huidan Li; Jie Zhang; Rongfen Huo; Haichuan Li; Baihua Shen; Ningli Li (Elsevier, 2016)
It has been widely accepted that macrophages are divided into M1 "pro-inflammatory" macrophages and M2 "anti-inflammatory" macrophages and an uncontrolled macrophage polarization plays an important role in the pathogenesis of different diseases. As the main substance of total glucosides of peony, paeoniflorin (PF), has been widely used to treat autoimmune and autoinflammatory diseases for years. Mechanistically, PF has been found to alter activities of many immune cells, which could further reduce inflammation and tissue damage. However, whether and how PF affects macrophages activities in vitro remains unknown. In current study, using M1 and M2 cells generated from mouse bone marrow precursors, we explored the role of PF in regulating M1/M2 cells activity in vitro. The results showed that PF inhibited LPS-induced M1 activity by reducing iNOS expression and NO production via decreasing LPS/NF-κB signaling pathway; whereas, PF enhanced IL-4-provoked M2 function by up-regulating Arg-1 production and activity via increasing IL-4/STAT6 signaling pathway. Our new finding indicates that PF can suppress M1 cells activity and enhance M2 cells function simultaneously, which could help to ameliorate autoimmune and autoinflammatory diseases in clinical treatment.